2008
DOI: 10.1111/j.1440-1843.2008.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbocisteine can scavenge reactive oxygen species in vitro

Abstract: These results suggest that carbocisteine could exert anti-inflammatory and anti-oxidant effects through directly scavenging ROS in addition to its previously known mucoregulatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
3
25
0
1
Order By: Relevance
“…However, CARB, at the selected concentration (10 −4 M), resulted less potent in controlling ROS formation in a nasal epithelial cell line and in another airway epithelial cell line (Nogawa et al 2009). Furthermore, in bronchial epithelial cells, carbocysteine, but not FP, was able to counteract the oxidant activities of CSE, also increasing GSH, HO-1 and Nrf2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, CARB, at the selected concentration (10 −4 M), resulted less potent in controlling ROS formation in a nasal epithelial cell line and in another airway epithelial cell line (Nogawa et al 2009). Furthermore, in bronchial epithelial cells, carbocysteine, but not FP, was able to counteract the oxidant activities of CSE, also increasing GSH, HO-1 and Nrf2.…”
Section: Discussionmentioning
confidence: 96%
“…16-HBE, an immortalised normal bronchial epithelial cell line (Cozens et al 1992), RPMI 2650a, a nasal epithelial cell line (Pace et al 2012a), and a mucin-producing human NCI-H292 airway epithelial cell line (Nogawa et al 2009) were used in this study.…”
Section: Stimulation Of Epithelial Cell Linesmentioning
confidence: 99%
“…Consistent with literature reports [1,2] , we found that carbocisteine was effective in reducing the rate of acute exacerbations and improving quality of life in patients with chronic obstructive pulmonary disease (COPD) in a large-scale multi-center clinical trial [3] . Despite the lack of a free thiol group, carbocisteine harbors a thioether group that can be oxidized by reactive oxygen species (ROS) [4] . Carbocisteine reportedly scavenged H 2 O 2 , HOCl, OH* and ONOO -in cell-free medium, inhibited ROS production in rat neutrophils [4] , promoted GSH and HO-1 expression in cigarette smoke-exposed bronchial epithelial cells [5] , and ameliorated oxidant-induced 16HBE cell apoptosis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…L-Carbocisteine inhibits inflammation associated with influenza virus infection and chronic obstructive pulmonary disease (Yasuda et al, 2006;Zheng et al, 2008;Yamaya et al, 2010;Asada et al, 2012), suppresses oxaliplatininduced hepatocyte toxicity by inhibiting oxaliplatin-induced decreases in the Bcl2/Bim ratio, and inhibits oxaliplatininduced apoptosis in vitro . Moreover, L-carbocisteine possesses free radical-scavenging and antiinflammatory properties in vitro (Zheng et al, 2008;Nogawa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, novel biologic activities of L-carbocisteine have been reported in the context of inhibition of inflammation associated with influenza virus infection and chronic obstructive pulmonary disease (Yasuda et al, 2006;Zheng at al., 2008;Yamaya et al, 2010;Asada et al, 2012). Another report showed that L-carbocisteine possessed free radical-scavenging properties in vitro (Nogawa et al, 2009). Various inflammatory cells, including neutrophils, mast cells, natural killer cells, macrophages, and dendritic cells, are involved in the induction and promotion of angiogenesis (Noonan et al, 2008;Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%